Onze Revolutie Bloemlezing uit de Indonesische geschiedschrijving over de strijd voor de onafhankelijkheid, 1945-1949 - Abdul, Wahid; Yulianti (Onafhankelijkheid, Dekolonisatie, Geweld en Oorlog in Indonesië 1945-1950, 2023)
Our Revolution contains a selection of translated Indonesian articles about the Indonesian Revolution (1945-1949) and the significance of that revolution for the development of the nation. The articles - written by contemporaries and academics of several generations - show the complexity of the Indonesian Revolution and see the struggle for independence, as well as developments in Indonesian thinking about it. National and local developments interacted. The struggle of the Indonesian population and armed groups against the British and the Dutch, the flaming enthusiasm of the Indonesian youth, the great social unrest and also a very diverse local and regional dynamic are discussed. This anthology offers a fascinating insight into the Indonesian historiography of the revolution.